Integrated Business Solution as a New Enterprise in The Tight Market of Interior Design Service Industries and Digital Media Competition - Prakasha, Reza; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. The objective of this paper is to develop integration strategy in term of Business Strategy, Marketing and Product Development. The Business Strategy focused on Business Model, The Marketing exposed about Marketing Strategy and Plan, while Product Development is planning about Digital Services Innovation. PT. Presisi Tata Kreasi itself created on July 14th 2014. It is run the Commercial or Corporate Interior segmentation of Architecture Services which parts of Creative Industries. Base on the tight competition and the declining economic situation nowadays, several industries cut their marketing budget and impact to the income or revenue of the mostly creative industries, especially the niche commercial interior segment. The company in this segment must take several action survive in very tight competition, including PT. Presisi Tata Kreasi. Otherwise the company will be eliminate too soon by the economic situation. This study of PT. Presisi Tata Kreasi business is used interview and questionnaire for consideration and guidance making decision. The result is; environment: direct competitor aggressiveness and tight competition in the industries. Management: The supply chain of PT. Presisi Tata Kreasi are not having strong agreement with the suppliers, cause to the cash flow of the company. Measurement: there are wide gap between the consumer perception and satisfaction of product/service quality. Marketplace: consumer segmentation that PT. Presisi Tata Kreasi targeting are not match with its value proposition. Method: the method that PT. Presisi Tata Kreasi use are very conventional.The business solution; first is short term solution which is Business Model Improvement that trying to solve the management problem. Second is mid-term Solution which is Marketing Strategy are trying to solve marketplace and method problems. And third is Long term Solution which is New Product/service innovation are trying to solve environment and measurement problems. Keywords: interior industries, root cause analysis, marketing strategy, services innovation, business model